The speeds and accelerations of the galaxies movements according to redshift measurements - Skeivalas, Jonas; Parseliunas, Eimuntas (International Conference “Environmental Engineering”, 2017)
The theoretical presumptions and some experimental calculations to analyse the speeds of the galaxies movements according to redshift measurements applying the Doppler effect are presented. The speed of the galaxy movement is treated as multidimensional continuous value, when values of the speed vector are calculated according to measurements of the redshift parameter z at corresponding moments of the universe lookback time. The most reliable values of the galaxy speeds vector are calculated applying the least square method to the vector of z measurements and including the additional parameters to eliminate the possible systematic errors. The acceleration of the galaxy movement is calculated as a speed fluxion according to period of the adopted redshift signal frequency and as a speed change during the lookback time interval. The expressions of functions of the galaxies speeds and accelerations are received by the polynomial approximation, when values of the polynomial parameters are calculated by the least square method.
Keywords: galaxies: evolution; galaxies: distances and redshifts; galaxies: kinematics and dynamics